KAJIAN SPILLWAY ROUTING PADA KONSTRUKSI BANGUNAN AIR DENGAN SISTEM POND UNTUK OPTIMALISASI PENGENDALIAN BANJIR DI KAWASAN INDUSTRI - Miskar Maini; Junita Eka Susanti (Jurnal Infrastruktur, 2025)
Ponds are key structures in flood control strategies, especially in industrial areas which have a high vulnerability to excess air runoff. The main risk faced is the potential for air overflow from the pond, which could cause serious damage downstream, including the risk of embankment failure and damage to the spillway. Therefore, controlling the water level in the pond is very important, especially in dealing with high-intensity flooding events. When the water level reaches the specified threshold, the water in the pool must flow in a controlled to the drainage channel through the spillway. This research uses the HSS Nakayasu method to estimate flood discharge entering the pond. At the same time, the calculation of the spillway is carried out based on the reservoir capacity of the pond and the planned spillway design. The research results show that the flood discharge entering the pond at various return periods, namely 5, 10, 20, 25, 50, and 100 years, ranges from 19.53 m³/s to 33.78 m³/s. The discharge from the spillway varies from 5,03 m³/s to 8,68 m³/s at the same return period. The maximum flood water level above the spillway varies from 0,90 m to 1.30 m, with the increase in water level from the bottom of the pond (elevation +20.00 m) reaching +24.90 m to +25.30 m. Further calculation results show that at a return period of 100 years, the pond is able to reduce flood discharge by up to 74%, with 26% of the flood discharge being channeled gradually through spillways and drainage channels to the river. The effectiveness of the spillway in reducing the risk of runoff confirms that this pond functions as a reliable flood mitigation solution for the shoe factory industrial area in Pekalongan Regency, Central Java Province.